Territorial Basis of the Status of Languages in the Islamic Republic of Afghanistan - Nayim Artash, Puhanmal Master Muhammad (Integrated Journal for Research in Arts and Humanities, 2023)
Many writers have written many articles and books about the status, territorial and country status of languages in Afghanistan. However, no articles have been written about the Uzbek language in Afghanistan, and the articles that have been written are insufficient and incomplete. This article, with the consideration of modern research methods, reveals the controversy between the Pashto and Dari languages, and the Uzbek language in the territory of the country. Showing its location and problems, the shortcomings and advantages of the Uzbek language in the past hundred years are described in detail. This article fully explains the situation of languages in the Afghan community.